Dynamic Impact of Income Inequality on Carbon Dioxide Emissions in Africa: New Evidence from Heterogeneous Panel Data Analysis - Ali, Hamisu Sadi; Hassan, Sallahuddin; Kofarmata, Yusuf Ibrahim (International Journal of Energy Economics and Policy, 2016)
We extended the study of Zhang and Zhao (2014) for China, which examines the regional impact of carbon dioxide emissions on income inequality. The present article examine the dynamic impact of income inequality on carbon dioxide emissions in Africa. We applied heterogeneous panel ARDL techniques of Mean Group (MG) and Pooled Mean Group (PMG) suggested by Pesaran et al. (1999), during 1984-2001. The main empirical result reveals that; the relationship between income inequality and carbon dioxide emissions is negative and statistically significant. This means that; widening income inequality could lead to the reduction of carbon dioxide emissions in the sampled countries. Moreover, the variables of trade openness, per-capita GDP, and urbanization are positive and statistically significant; this means that increase in any of these variables could lead to overall increase in the level of carbon dioxide emissions. Therefore, in providing policies that will be used to improve environmental quality in Africa, income inequality should not be considered because it is reducing the level of environmental degradation through reduction of carbon dioxide emissions. Hence, policy makers should not consider income inequality when formulating environmental policies among the selected sample countries. Keywords: Income inequality, emissions, Mean Group, Pooled Mean Group, Panel ARDL, Africa JEL Classifications: F64, Q54, Q58